1997
DOI: 10.1161/01.atv.17.10.2103
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Coronary Heart Disease and Activation of Factor XII in Middle-Aged Men

Abstract: Increased activity is known to be present in the extrinsic, intrinsic, and final common pathways of the hemostatic system in men at high risk of coronary heart disease (CHD), but the status of the contact system of coagulation in this condition is uncertain. Plasma levels of activated factor XII (XIIa), the initial product of contact activation, have therefore been measured by ELISA in 2464 men aged 51 to 62 years, clinically free of CHD, who were taking part in a prospective cardiovascular survey based in gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
52
4
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 29 publications
5
52
4
1
Order By: Relevance
“…This would suggest that the effect of factor XII on risk is not by activation of factor XI, but by an alternative mechanism. Previous studies have suggested that plasma levels of factor XIIa are related to plasma levels of cholesterol and triglyceride, 23,27,28 but not HDL cholesterol. 22 The present study corroborates these findings.…”
Section: Discussionmentioning
confidence: 91%
“…This would suggest that the effect of factor XII on risk is not by activation of factor XI, but by an alternative mechanism. Previous studies have suggested that plasma levels of factor XIIa are related to plasma levels of cholesterol and triglyceride, 23,27,28 but not HDL cholesterol. 22 The present study corroborates these findings.…”
Section: Discussionmentioning
confidence: 91%
“…This is in accordance with clinical evidence that elevated levels of FXII(a) positively associate with arterial thrombosis, ischemic stroke, and coronary heart disease. [29][30][31] On the contrary, conflicting evidence exists on whether individuals with partly reduced FXII levels have an increased risk of cardiovascular disease (reviewed in Renné et al 15 and Woodruff et al 16 ). In this regard, the thrombus-destabilizing effect observed under conditions of reduced FXII activity needs more attention.…”
Section: Discussionmentioning
confidence: 99%
“…9 -11 Factor XII is a plasma protein and a member of the serin-protease family. [12][13][14] Once activated, it initiates the contact activation system; it also has fibrinolytic properties. 15 Severe congenital Factor XII deficiencies have been described, but its association with thromboembolic complications is controversial.…”
mentioning
confidence: 99%
“…10 Some studies have reported that variability of plasma Factor XII levels are associated with the predisposition to arterial thrombosis. 13,14 A common genetic polymorphism (46 C to T substitution) in the 5Ј-untranslated region of the coagulation Factor XII gene has been associated with low translation efficiency and variability of Factor XII levels in the general population. 12 Association studies have shown the relationship of Factor XII levels and the 46 C3 T polymorphism in the development of arterial disease, but the results are controversial.…”
mentioning
confidence: 99%